Land and marine hydrogeology - Taniguchi, Makoto, 1959-; Wang, Kelin, 1956-; Gamō, Toshitaka; ScienceDirect eBooks; International Forum on "Water and Life" (2000 : Okayama International Center) (Amsterdam : Elsevier, 2003)
This volume represents an effort to bring together communities of land-based hydrogeology and marine hydrogeology. The issues of submarine groundwater discharge and its opposite phenomenon of seawater invasion are discussed in this book from the geophysical, geochemical, biological, and engineering perspectives. This is where land hydrogeology and marine hydrogeology overlap. Submarine groundwater discharge is a rapidly developing research field. The SCOR and LOICZ of the IGBP have recently established a working group for this research. IASPO and IAHS under IUGG also recently formed a new joint committee "Seawater/Groundwater Interactions" to collaborate with oceanographers and hydrologists. The other articles introduce frontier research topics in more typical land and marine environments, such as fluid flow in karst aquifers, the biological aspects of fluids in sedimentary basins and submarine sedimentary formations, respectively, and vigorous fluid flow in subsea formations and their significance in global tectonics. Geochemical characteristics of hydrothermal activities at a number of active continental margins are also reviewed, and multidisciplinary geophysical constraints of the permeability of young igneous oceanic crust are summarized. A variety of driving mechanisms for fluid flow is discussed in land and subsea formations; terrestrial hydraulic gradient, buoyancy driven free convection, tidally induced flow, flow induced by tectonic strain, flow due to sediment compaction.
Assessment methodologies for submarine groundwater discharge / M. Taniguchi, W.C. Burnett, J.E. Cable and J.V. Turner -- Radon tracing of submarine groundwater discharge in coastal environments / William C. Burnett, Jaye E. Cable and D. Reide Corbett -- The chemical characteristics of submarine groundwater seepage in Toyama Bay, central Japan / J. Zhang and H. Satake -- Prospects of engineering applications of submarine-groundwater-discharge research in Japan / Hideaki Miyamoto and Tomochika Tokunaga -- Evaluation of seawater intrusion accompanying the coastal coalmine excavation in the Joban coalfield area, Japan / J. Shimada, K. Kojima, K. Ohara and M. Yamakawa -- Natural tracing in karst aquifers / Michel Monnin and Michel Bakalowicz -- Abundance and viability of subsurface microbial communities in sedimentary and igneous rock aquifers / Y. Murakami, Y. Fujita, T. Iwatsuki and T. Naganuma -- Stable isotopic compositions of bacterial light hydrocarbons in marginal marine sediments / F. Nakagawa, U. Tsunogai, N. Yoshida and D.D. Adams -- Submarine hydrothermal activity in coastal zones / Toshitaka Gamo and Geoffrey P. Glasby -- High permeability of young oceanic crust constrained by thermal and pressure observations / Kelin Wang and Earl E. Davis.
Internat. conference proceedings.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Hydrogeology; Hydrogeology -- Congresses; Groundwater flow; Groundwater flow -- Congresses; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Groundwater flow; Hydrogeology; Hidrogeologia; Electronic books